Pemahaman terhadap Lafadz Makr, Kaid, dan Khida‘ Dalam Al-Qur’an Surah Ali Imran Ayat 54 dan Al-Baqarah Ayat 9: Analisis terhadap Penafsiran Syeikh Abdurrahman bin Nashir Assa'di Dalam Tafsir As Sa'di - Azmi, Ulul; Andy, Safria; Sari, Winda (Ikatan Da'i Indonesia, 2023)
In this day and age, it is an age when the outbreak of deceit, there are many bad effects caused by the perpetrators of deception. Tipu in the Koran is mentioned in many verses with different patterns but has similarities in terms of meaning, or known as Taraduf or Mutaradif (Different words but have the same meaning), then it is necessary to be careful what they mean, so what if the deeds of the Deceivers are directed at Allah, because for some people are afraid to interpret deceit in Makr language, Kaid, Khida' if placed for Allah, because they think Allah cannot have the nature of deceit, this is the problem, especially among the claimants of Shari'a science. The research approach used by the author in this study is a Qualitative approach and uses descriptive and comparative analysis methods or Muqorron, namely by comparing verses with verses, with hadith or with the opinions of interpreters so that various interpretations are found that may have When talking about Makr, Kaid, and Khida',Sheikh Abdurrahman bin Nashir Assa'di did not talk in too much detail about the lafadz but he only interpreted in general terms what Makr, Kaid, and Khida' were and the essence of the three lafadz in the Koran, when he interpreted the verse about Makr, then what appeared was the planned deceit, when he interpreted Khida', So what arises from his interpretation is the same deed but the way it is different. Which Makr, Kaid requires there to be planning, while Khida' can be done without planning.